Response to On prompt update of literature references in the Protein Data Bank. (1st October 2014) - Berman, Helen M.; Burley, Stephen K.; Kleywegt, Gerard J.; Nakamura, Haruki; Markley, John L.
<x xml:space="preserve">Abstract</x> The wwPDB responds to the article On the prompt update of literature references in the Protein Data Bank [Wlodawer (2014), Acta Cryst. D70, 2779].